The Design of Thai Dog Breed Art Toys through a Three-Dimensional Modeling Process to Promote Awareness of Stray and Disabled Dogs in Thailand - ก้อนสุวัน, รุ่งทิวา; เขื่อนแก้ว, ปรานต์; ดีเจริญชิตพงศ์, จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The research entitled “Designing Thai Dog Breed Art Toys through a Three-Dimensional Modeling Process to Promote Awareness of Stray and Disabled Dogs in Thailand” aims to: (1) study and analyze information related to Thai dog breeds in terms of their physical characteristics, temperament, and unique identities of each breed; (2) study and develop skills in three-dimensional (3D) modeling for art toy design; and (3) design and produce art toys inspired by Thai dog breeds, stray dogs, and disabled dogs, with the completed works delivered to the Soi Dog Foundation.           This study employed a creative research approach, involving the collection of data from documents, related studies, and field research. The collected data were analyzed and synthesized to develop design concepts, followed by the creation of conceptual sketches and the design of four art toy characters: a dog with a trash bin, a dog with old toys, a dog in a state of fear, and a disabled dog. Three-dimensional modeling software was used to develop the prototypes. The research instruments included a content quality evaluation form, a media quality evaluation form, and a satisfaction questionnaire. Data were analyzed using descriptive statistics, including mean and standard deviation.           The research findings revealed that the overall mean score of content quality evaluation by experts was 4.08 (S.D. = 0.91), representing a high level, while the overall mean score of media quality evaluation by experts was 4.08 (S.D. = 0.70), also at a high level. In addition, the satisfaction assessment of 30 participants interested in dogs showed a mean score of 4.60 (S.D. = 0.56), indicating the highest level of satisfaction. These findings suggest that the developed art toys demonstrate strong content and media quality and are effective in promoting awareness and audience satisfaction.